'My father's hammer never ceased its song day and night': the Zulu ferrous metalworking industry - Maggs, T. (Southern African Humanities, 2021)
In this paper an attempt is made to reconstruct patterns of organisation in the precolonial ironworking industry of the Natal-KwaZulu region. Early written sources have, until recently, been the basis of academic descriptions of the industry, but they are often unreliable. Recent archaeological findings together with oral evidence, some of it unpublished, provide a much firmer basis for reconstruction. Attention is focused on the Nkandla industry as the main source of ferrous artefacts for the Zulu kingdom. To cite this article: Maggs, T. 1992. 'My father's hammer never ceased its song day and night': the Zulu ferrous metalworking industry. Natal Museum Journal of Humanities 4: 65-87.